(untitled) (Vietnam Journal of Community Medicine, 2021)
Objective: To investigate the situation of treatment compliance and factors related to treatment compliance of gastroenteritis of outpatients at the gastrointestinal department of Vinh Long General Hospital. Objects and methods: Study of retrospective cross-sectional description on 310 medical records of patients over 18 years old diagnosed with gastroenteritis, outpatient treatment at the internal department, Vinh Long General Hospital from November 2019 to July 2020. Results: Compliance rate of the study group of patients was quite high, 94.19% (292/310) complied with treatment and 5.81% (18/310) did not comply with treatment according to the doctor. There was 96.58% good drug compliance - high level and 3.23% good drug compliance - low level. Most patients got better and got better after treatment: The rate of patients recovered from the disease and reduced all clinical symptoms of the disease was 30.32% (94/310). The rate of patient declined disease 56.45% (175/310). There was a relationship between compliance and eradication rate H.p. There was a relationship between education, living status, economic status and adherence to treatment. There was a link between health official’s support and patients’s adherence to treatment. Conclusion: Adherence rate was high. There was a high proportion of patients with curable treatment results and relief from their symptoms. There was a relationship between compliance and eradication rates, education level, economic conditions and support of health workers.